P3 Oxidative Distress and Antioxidants in Severe Asthma. (19th November 2012) - Sathyamurthy, R; Manney, S; Webster, C; Krishna, T; Perkins, G; Mansur, AH
Abstract : Background: The role played by oxidative stress (OS) burden and antioxidant (AO) defences in severe asthma (SA) have been inconsistent. Aims: To compare levels of OS markers and AO between subtypes of SA, mild asthma (MA) and control (N). Methods: A longitudinal case control study (2009–2010) included 15 N, 15 corticosteroid naïve MA, 10 SA not dependent on oral corticosteroids (OCS), 10 SA dependent on OCS (NOCS) and 10 type-1 brittle asthma (BA). Subjects taking vitamin supplementation were excluded. Serum AO – vitamin A (vit-A) and E (vit-E), copper(Cu), selenium(s) and zinc (Zn) were measured at first visit. Exhaled breath condensate (EBC) nitrate and 8-isoprostane(iSo), Fractional exhaled Nitric Oxide (FeNO) were measured on 3 visits 3 weeks apart as markers of OS. OS and AO markers were correlated with asthma-severity. Results: Sixty subjects were recruited (16 males, age 19–57 yrs). 8-iSo was not detectable in all of our samples. Significant correlations (p<0.05) between AO and OS markers are given in the table below Between group analyses revealed correlation of FeNO with increasing asthma-severity, but EBC nitrate did not differ significantly amongst the 5 groups. Vit-A was significantly higher in OCS group, and vit-E was significantly higher in the OCS, NOCS and BA groups as compared to N. There was no significant difference between the 5 groups in Cu, Zn or Se levels. Regression analysis identified age, height, and vit-E as best predictors of FEV1. Conclusion: This study indicates paradoxically increased levels of some of the AO in severe asthmatics. We hypothesise that the mechanics by which AO counteracts the OS in severe asthmatics could be impaired rather than AO deficiency. This needs to be researched further in larger studies.